INTEGRASI BUDAYA KEWIRAUSAHAAN KE DALAM PEMBELAJARAN MATA KULIAH RESTORAN - Titin Hera Widi Handayani (Jurnal Cakrawala Pendidikan, 2008)
This researchintended to conduct the integrated entrepreneurship cultureimprove the subject of Restaurant, so that study can be more effective and qualifiedin the future Peculiarly this research intended to find out the methods or learningstrategicin integrating entrepreneurship and to know the result reached bystudents in integrating entrepreneurship study at management aspecL The subjectof this researchwas students who taken the subject of Restaurant at UndergraduateProgram of Food and Fashion Engineering Education The object is integratedentrepreneurship culfurizationwith the subject of Restaurant at managementaspecL Research procedure is conducted based on action research method whichare planning, action, observation and reflection, treated in 6cyc1es The result ofresearch indicatesthat the integration of entrepreneurship culture can improve themanagerial competencyof students at subject of RestauranL Gradually, thecompetency was increasing from first rotation to sixth, that is at non formalrestaurant group,equal to 10 % with the average improvement of 2 %, formalrestaurantgroup 27,5 % with the average improvement of 5,5 %, and cake bakerygroup 10% with the average improvement of 2 % The result of action executionshowsthat the step of study consisted of (a) modules learning, (b) field visiting (c)business plan making, (d) implementation of business plan, (e) monitoring,reflectingand evaluating, which is applicable to improve the study quality